Synthesis and Characterization of Covalent Triazine Framework CTF-1@Polysulfone Mixed Matrix Membranes and Their Gas Separation Studies - Dey, Subarna; Bügel, Stefanie; Sorribas, Sara; Nuhnen, Alexander; Bhunia, Asamanjoy; Coronas, Joaquín; Janiak, Christoph (Frontiers in Chemistry, 2019)
Covalent triazine framework CTF-1 and polysulfone (PSF) are used to form mixed-matrix membranes (MMMs) with 8 wt%, 16 wt% and 24 wt% of the porous filler material CTF-1. Studies on permeability and selectivity are carried out concerning the gases O2, N2, CO2 and CH4. CO2 permeability of the synthesized MMMs increases by 5.4 Barrer in comparison to the pure PSF membrane. The selectivity remains unchanged for O2/N2 and CO2/CH4 but was found to be increased for CO2/N2. Further, comparisons to theoretical models for permeability prediction yield a permeability for CTF-1 which is about six times higher than the permeability of PSF. The inverse of the sum of the free fractional volumes (FFV) of the polymer and the filler correlate linearly to the logarithm of the permeabilities of the gases which conversely indicates that the porosity of the filler contributes to the gas transport through the membrane.